The principle of establishing relationships between the results of non-specific and specific test exercises performed by hockey players - Pavlov, A.S.; Bizyaev, V.V.; Frolova, N.N.; Pozdeeva, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to establish the relationship between the results of speed test exercises performed by young hockey players and the frequency of their use in training microcycles. Methods and structure of the study. Young hockey players of various age groups participated in the study. During the study, team coaches were surveyed, pedagogical observations of the training process were conducted, and hockey players were tested. The results of selected speed test exercises and the frequency of their combined use in training microcycles were evaluated. Correlation coefficients between the results of these test exercises were calculated. Results and conclusions. Significant differences were found in the frequency of combined use of selected exercises in training microcycles and in the correlation coefficients of test exercise results. It was established that the levels of correlation between the results of speed test exercises performed by hockey players are determined by the frequency of combined use of these exercises in training microcycles.